Taxing Collaborative Software Engineering: The Challenges for Tax Compliance in Software Engineering - Dorner, Michael; Capraro, Maximilian; Treidler, Oliver; Kunz, Tom Eric; Smite, Darja; Zabardast, Ehsan; Mendez, Daniel; Wnuk, Krzysztof (IEEE Software, 2024)
The engineering of complex software systems is often the result of a highly collaborative effort. However, collaboration within a multinational enterprise has an overlooked legal implication when developers collaborate across national borders: It is taxable. In this article, we discuss the unsolved problem of taxing collaborative software engineering across borders.
CRIS-Team Scopus Importer:2024-06-21